Factors associated with the delay in seeking inpatient and outpatient care services in the Philippines - JJ Capuno; AD Kraft; LC Poco; SA Quimbo; CAR Tan (University of the Philippines, School of Economics (UPSE), 2017)
Despite the country's policies and programs towards universal health care, health is not improving as well as expected, which suggests that households still face significant barriers to their choice of and access to health care, and their timing of use of health services. Using a nationally representative sample of households, we investigate the factors that affect the timing of outpatient care and inpatient care utilization. We define two indicators of delay in seeking care, namely: one for outpatient care, as the number of days from onset of symptom until visit of a clinic or provider, and another for inpatient care, as the number of days from doctor's advice until hospital confinement. Given our dependent variables are measured in terms days until visit, we estimate proportional hazard models (Cox, Weibull and Gompertz) to identify the significant factors associated with delay in seeking health care services. The factors associated with delay are classified in terms of health needs, financial access, physical access, opportunity costs, other household factors and location. Our findings suggest health needs and opportunity costs are the main factors associated with the delay in seeking outpatient and inpatient care services among Filipinos in need of medical attention. Perhaps more importantly from a policy perspective, we also find that physical and financial access variables do not significantly affect timing of care. We draw some implications from the results on increasing access to health care, through improvements in awareness of social health insurance and in the actual quality of health facilities. We also identify directions for future research.
Keywords: I12; D12; I19; 330; Outpatient care; inpatient care; delay in seeking health care; health care utilization; social health insurance; Philippines